Análise da biologia reprodutiva em Acacia mearnsii De Wild. (Fabaceae) - Alves, Eudes Maria Stiehl (2007)
The black wattle (Acacia mearnsii De Wild., Fabaceae) is one tree species cultivated in Rio Grande do Sul since the middle of the 1930decade. It is a species that presents a great ecological importance because of its fast growth and high potencial for degraded soils recovery. Besides, the black wattle cultivation provides a broad range of products for the chemical industry. Due to these reasons, it is a species that have been widely cultivated in this state since its introduction. Nowadays the cultivated area is estimated above 160.000 ha and distributed principally in small properties. Although it has a considerable economic importance, the expansion of the cultivated area of A. mearnsii has been limited mainly due to of the lack of genetically superior seeds. Then, perform decisions to control crossings by a program of genetic improvement for black wattle has been justified. The knowledge of reproductive biology in forest tree species is very important to programs of genetic improvement, because it provides knowledge on the pattern of kinship among individuals a given population. So, the aim of this study was analyze some aspects of the reproductive biology in A. mearnsii. The study of phenology has being considered an important tool for the comprehension of strategies developed by plants for species prepetuation. Moreover, its information has permited the developmet of strategies of management, forest resources conservation, genetic improvement and the intensive monitoring of climate changes and its reflexes on vegetation. Nowadays the association of remote sensing technology with phenological information has permited the rapid analysis of ecosystems dynamic, the monitoring of the advances of areas of human occupation, a differentiation of vegetational physionomies and the performing of decisions in terms of biomass production, by the utilization of information related to the reflectance of the target in length of waves of the red visible region and that of the adjacent infrared. Through this revision it was verified the importance of phenological analysis in studies that aim to comprehend the events linked to life cycle of plants and its interaction with the environment. Moreover, this it now leoked for information on the efficiency of the interaction of phenological studies and the remote sensing technology for the analysis of forest ecosystems dynamic. Throughout the analysis of germination in vitro and of viability by the colorimeter method it was evaluated the contribution of male gametes of trees of one seed production area for the fecundation of black wattle. In the germplasm evaluated it was observed a high germination mean (73%). However, the pollen tube emission mean was low (23%). In the other hand, the viability observed by the colorimeter method was high (100% of viable polyads in five trees), indicating that the colorimeter method have superestimated the real viability. The flowering and fructification of Acacia mearnsii De Wild were analyzed in trees of a provenanceprogeny test and in a commercial plantation in the years of 2001 and 2002. By the index of activity it was verified the existence of a synchronous formation of flowerbuds, in the provenance-progeny test (in 2001, 92.8% and in 2002, 70%) as soon as in the commercial plantation (in 2002, 97%). The opening of flowers was also synchronic in the provenance-progeny test (in 2001, 85.6% and in 2002, 66%) and in the commercial plantation (in 2002, 78%). The formation of fruits was synchronic and occurred immediately after the top of flowers opening. The period of development and maturation of fruits was completed in twelve months, followed by the dispersion of seeds. The Morisita Index confirmed the seasonality of the phenological events. The stigma receptivity of A. mearnsii was analysed in different trees of one seed production area and were compared the periods of stigma receptivity and of pollen viability in many phases of flower opening. It was used the colorimeter method of Baker’s reagent to indicate the receptivity and the viability. The analyses were conducted in completely randomized design and the χ² statistic was used to verify the significance of the events studied. It was observed the receptivity in the beginning of flower opening (71%), reaching the total receptivity (100%) at the anthesis. It was detected pollen viability in the beginning of anthesis (77%) and in the total flower opening (88%). In the stage of senescence there were detected receptive stigmas (50%) and viable polyads (23%). To investigate the possibility of occurrence of seed production by selfing were used trees of one commercial plantation in the year of 2004. Through the index of self-incompatibility it was identified the existence of cross pollination in the majority of the events (ISI=0.134). Through the ANOVA it was detected significant difference between isolation (cellophane and tissue-no-tissue) and absence of isolation of the inflorescences. Treatment means comparision was performed through Tuckey’s test. The open pollination fruit formation was superior ( X = 157.9 ), followed by the isolation of tissue-no-tissue bags ( X = 11.8 ) and by cellophane bags ( X = 10.5 ). There were evidences that the ability of germination of the polyads was influenced by the genotype, suggesting that one of the factors that contributes for the restrict formation of seeds could be the crossing among related individuals, fact reforced by the analysis of self-incompatibility, that evidenced the presence of mechanisms of selfing prevention in the germplasm evaluated. There is superposition of pollen viability and female receptivity stages, what increases chances of selfing. Fecundation is not limited by receptive stigmas in the inflorescences, because the majority of the trees analysed in the seed production area contributed completely with receptive stigmas.